Virtual Learning Of Deaf Students: We Miss Pupils, We Hate Covid19 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advent of Covid-19 seems to create limitations in everyday life. Many things had to be restricted and restrained because of the threat of artistic creatures invisible to the naked eye. Our hustle and bustle in living a life full of these SOPs makes us sometimes creative, sometimes lost cause. All aspects lose authority. Including the most important thing which is education. Discussion is devoted to special education. Many of the students with special needs (MBK) are left behind in receiving knowledge because they cannot go to school for a long time due to the movement control order (PKP). This qualitative study was conducted to examine the perceptions, feelings and expectations of special education teachers with hearing problems on this condition. The majority of them expressed their longing for the implementation of teaching and learning (PDP) as usual in the physical classroom. The results of this study are expected to provide an overview of the situation that occurred in the world of special education when this pandemic hit.